Fast synthesis of VC and V2C nanopowders by the mechanochemical combustion method. (July 2015) - Hassanzadeh-Tabrizi, S.A.; Davoodi, Danial; Beykzadeh, Ali Asghar; Chami, Akbar
Abstract: VC and V2 C nanopowders were synthesized by the mechanochemical combustion method in a high-energy ball mill. The synthesized powders were studied by X-ray diffraction (XRD), differential thermal analysis (DTA), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). According to X-ray diffraction the product predominantly consists of VC and V2 C phases after 80 min milling without further heat treatment. The TEM results show that vanadium carbide nanopowders are mainly composed of nearly spherical particles with a mean diameter of about 40 nm. Thermodynamic calculations show the reaction to be a mechanically induced self-sustaining one (MSR). Highlights: VC and V2 C were synthesized via mechanochemical synthesis without further heat treatment. The synthesized powders were studied by XRD, DTA, SEM and TEM. Nanopowders had a mean diameter of about 40 nm.